Endoscopic transnasal repair of CSF rhinorrhea: Techniques and out come (Bangladesh Journal of Otorhinolaryngology, 2011)
Background: Endoscopic transnasal repair of CSF (Cerebro Spinal Fluid) fistula is safe, effective and widely accepted minimally invasive procedure. We describe our experience of techniques and result of endonasal CSF fistula repair along with its safety and effectiveness as well as low complications. Method: All patients who underwent endonasal CSF fistula repair from July ’07 to September ’09 in the department of Neurosurgery, Dhaka Medical College Hospital & Islami Bank Central Hospital, Dhaka, Bangladesh were prospectively analyzed. Patients were followed up for average period of 10.2 months (Range: 3 to 30 months). Results: The age range was 12 years to 55 years; male -female ratio was 5:8. Clinical features were single nose rhinorrhea, double nose rhinorrhea, anosmia, history of trauma, history of transsphenoidal pituitary surgery, recurrent meningitis, aspiration pneumonia and insomnia, obesity and skeletal dysplasia. Etiology of CSF Fistula were idiopathic-06, congenital hydrocephalus-01, post head injury (traumatic)-05 and post surgical-01case. Anatomical sites of fistula that we found in our series were cribriform plate-06, posterior ethmoidal-04, planum sphenoidalae-02 and sellar-01. Post operatively, 2 patients complained of foul smelling within nose and 1 case had persistent CSF rhinorrhoea, where we over looked a frontal sinus fistula and was closed transcranially later on. There was partial nasal obstruction in 01 case that resolved after a year. New anosmia developed in 01 case after operation. Mortality was nil. Out of 13 transnasal endoscopic repair of CSF fistula 12 cured and 01 persisted (that was retreated by transcranial approach) Conclusion: Endoscopic transnasal CSF fistula repair is associated high success rate of fistula closure along with very few complications; at the same time it is minimally invasive, less traumatic and patient-friendly. So it is our notion that it should be the preferred approach to CSF fistula due to defect in anterior skull base and sellar floor. Key Words: Endoscopic Transnasal; CSF fistula; CSF rhinorrhea. DOI: 10.3329/bjo.v17i1.7618 Bangladesh J Otorhinolaryngol 2011; 17(1): 14-20